Effectiveness of Peppermint and Cough Aromatherapy on Sputuum Expeltion in Patients with Pulmonary Tuberculosis - Jojor Silaban; Zulfikri Zulfikri; Risdiana Melinda Naibaho; Verawaty Fitrinelda Silaban (Indonesian Journal of Global Health Research, 2026)
Pulmonary tuberculosis (TB) is a serious infectious disease with the main symptoms being a cough with phlegm and shortness of breath due to the accumulation of sputum in the respiratory tract. Indonesia is the country with the second highest number of cases in the world after India. Non-pharmacological therapies such as peppermint aromatherapy inhalation and effective coughing techniques are believed to help expel sputum, thereby improving the patient's respiratory function. Inhaling peppermint aromatherapy vapor and effective coughing can relieve breathing in pulmonary TB patients with a normal respiratory rate and facilitate sputum expulsion. This study aimed to determine the effectiveness of peppermint aromatherapy inhalation and effective coughing techniques on sputum expectoration in patients with pulmonary tuberculosis at the Batang Beruh Community Health Center in Dairi Regency in 2025. The study used a quasi-experimental design with a pretest-posttest control group design. It was conducted from April to November 2025. The sample consisted of 48 patients with pulmonary tuberculosis, divided into an experimental group (24 people) who received peppermint aromatherapy inhalation and effective coughing techniques, and a control group (24 people) who did not receive these interventions. Data were collected through observations of sputum expectoration before and after the intervention on an interval scale, analyzed using the Mann-Whitney test.The experimental group showed a significant decrease in sputum output scores from an average of 5.50 to 4.29 in the first intervention and from 4.83 to 3.46 in the second intervention. The control group did not show any significant changes. The results of the Mann Whitney statistical test showed a significant difference between the two groups (p = 0.000), proving that the peppermint aromatherapy inhalation and effective coughing interventions were proven to be effective in increasing sputum output in pulmonary tuberculosis patients.